A comparative study of Outcome in Ventriculoperitoneal Shunt and Endoscopic Third Ventriculostomy in Cases of Tubercular Meningitis with Hydrocephalus in Pediatric Patients - Averma, Abhijit Verma; Srivastava, Chhitij; Ojha, BK; Mittal, Siddharth; Yadav, Awadesh (Nepal Journal of Neuroscience, 2023)
Introduction: Tuberculous meningitis (TBM) is becoming a rare illness in industrialized nations, but it is still widespread in underdeveloped nations. Ventriculoperitoneal shunt surgery is the GOLD Standard and is time tested procedure. Shunts, however, are associated with multiple problems.Material and Method: This is an observational study that compares the outcome of Endoscopic Third Ventriculostomy (ETV) with Ventriculoperitoneal shunt in patients of TBM with hydrocephalus at a 6-month follow-up. This study was done at a single tertiary care center.  Data was collected from the patient records as per selection criteria. 100 consecutive cases in each ETV and Shunt group fulfilling selection criteria were included in the study.  The two procedures were compared for their clinical outcome based on modified Vellore grade at 6 months of follow-up.Discussion: Evaluation of outcome at 6 months revealed an overall success rate of 68.5%. The success rate was higher for shunt (71%) as compared to ETV (66 %).  However, the difference between the two groups was not significant statistically. For children with advanced TBM and elevated ICP, shunt surgery may not be necessary. While some authors have considered the potential of delaying surgery for these kids, others have argued that even a single positive outcome warrants shunt placement for every kid with tuberculous hydrocephalus.Conclusion:  In pediatric cases of TBM with Hydrocephalus ETV should be considered as a first-line treatment in lower grades of TBM. Though for definitive comparison, a long-term randomized study is needed, and the study to look into factors responsible for the failure of ETV in TBM cases needs to be identified to formulate an ETV success score.